NTERNALISASI NILAI KARAKTER RELIGIUS MELALUI PEMBELAJARAN AKIDAH AKHLAK DI MI MUHAMMADIYAH PUCANGAN - Asroriah, Fatimatul (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2022)
It is important to instill religious character education in elementary school students. This is motivated by the importance of efforts to cultivate the intelligence of students to be able to think and behave in accordance with the noble moral values of the Prophet. The purpose of the research is to describe the inculcation of religious character values in the learning of moral aqidah which includes planning, implementation, evaluation, obstacles and solutions encountered. The research approach and method chosen were descriptive qualitative. The research partner is MI Muhammadiyah Pucangan, Ngrambe sub-district, Ngawi Regency. Collecting data using observation, interviews and documentation. Planning for religious character education is carried out by preparing lesson plans and creating a conducive learning atmosphere. Instilling the qualities of Rasulullah must be integrated in every learning, both extracurricular and intracurricular. Evaluation of religious character education is carried out based on the 2013 Curriculum and refers to Permendikbud Number 66 of 2013 covering social attitudes and spiritual attitudes. The instruments and assessments were carried out through observation, student behavior journals, peer assessments, and muttaba'ah sheets. Religious character education programs are effective in instilling the moral character of the Prophet in students who are supported through the school's vision and mission and the availability of facilities, principal policies and exemplary support from each component in the school.